Patterns and Determinants of Income Diversification among Farm Households in the Northeast of Thailand - Charoenkittayawut, Sorrapong; Chulilung, Prapaporn; Suwanmaneepong, Suneeporn (King Mongkut's Agricultural Journal, 2023)
The objectives of this research were (i) to investigate the pattern of income diversification of farm households, (ii) to assess the level of income diversification among farm households using the Simpson index of diversification (SID), and (iii) to study the determinants of income diversification among farm households in the Northeast of Thailand. This research employed secondary data from the 2021 Household Socio-Economic Survey collected by the National Statistical Office, Thailand. The household samples selected in this research included farm households in the Northeast of Thailand according to the household socio-economic status classification of the National Statistical Office. Data were analysed for frequency, percentage, mean, standard deviation, and Tobit regression analysis. The finding revealed that the calculated share of non-farm income was slightly higher than that of farm income. Considering the level of income diversification using SID, the finding indicated that 49.99% of farm household samples had a medium level of income diversification, followed by the high and low levels at 25.71% and 24.30%, respectively. The highest proportion of economic activities that farm households participated in was ‘planting and forestry’ and 'other non-employment’, accounting for 95.91% and 95.17%, respectively. The Tobit regression analysis revealed that the age of the household head, the household size, household members migrating for domestic work and overseas work, and the amount of debt in the informal sector significantly and positively influenced income diversification among farm households in the Northeast of Thailand. In contrast, annual household income per capita and land size significantly and negatively affected household income diversification among farm households. However, the sex of the household head, the education level of the household head, the household dependency ratio, the amount of debt in the formal sector, access to credit, and the location of the household had no significant effect on income diversification among farm households in the Northeast of Thailand.